Changing Lives in Laos: Society, Politics, and Culture in a Post-Socialist State - Santamaria, Matthew (Kasarinlan: Philippine Journal of Third World Studies, 2018)
Review of Changing Lives in Laos: Society, Politics, and Culture in a Post-Socialist State , edited by Vanina Bouté and and Vatthana Pholsena.